Pengaruh Model Pembelajaran Examples Non Examples terhadap Hasil Belajar Siswa Pembelajaran PKn SD - Regita Anggraini; Ramanata Disurya; Farizal Imansyah (Departement of Mathematics Education, 2024)
This study aims to determine whether the Examples Non Examples learning model can improve Civics learning outcomes for fifth grade students at SD Negeri 10 Talang Kelapa. This research is a type of quantitative research using the experimental method of the True-Experimental Design research type in the form of a Posttest-Only Design . The variables of this study consist of the independent variable (X), namely the Examples Non Examples learning model and the dependent variable (Y), namely learning outcomes. The population of this study were 60 students in class VA and class VB SD Negeri 10 Talang Kelapa. The samples taken were 30 students in VA class as an experimental class who were taught using the Examples Non Examples learning model and 30 students in VB class as a control class who were taught conventionally. In taking samples using Simple Random Sampling. The data collection technique used in this study was tests, tests were used to improve student learning outcomes in Elementary Civics subjects. Data analysis technique uses the t-test formula. The calculation results show the value of t count > t table , namely 8,640 > 1.672, which means rejecting Ho and accepting Ha, so it can be concluded from the results of the study that there is an influence of the Examples Non Examples Learning Model on the Learning Outcomes of Civics Learning Students at SD Negeri 10 Talang Kelapa.